Time management behavior, job demand-resources and burnout among academicians - Nor Ajmah, Mohd Yassin (2015)
This study evaluated the effects of time management behavior, job demand, job resources towards Burnout. A review of the academic staff in the district to the north, Malaysia is also assessing the burnout experienced by workers in the academic fields. Respondents were 157 academic staff includes lecturers around northern Malaysia, UUM, UiTM Merbok, UniMAP and USM. The data collected were processed collectively using the Statistical Packages for Social Science (SPSS ver.20). The data were collected through the use of questionnaires and online form. Statistical techniques used were the percentages, cross tabulation, correlation, and multiple regression analysis for finding answers to research questions that formed. All three hypotheses were accepted that the value of multiple regression showed JD, JR and TMB significantly to burnout at levels not exceed 0.05. Multiple regression results also show that all these variables significantly to burnout and explain 33.6% (r² = 0.336, F = 25,823, p ≤ 0.05) total variance. The study also found that university management should take proactive steps to meet the demands of jobs and job resources, encourage employee time management behavior is observed mainly ensure that burnout does not happen in the workplace. Thus, the organization can give recognition to employees when they apply new knowledge in the workplace, provide financial resources for development and growth promoting employee participation in providing activities in the organization.